Diseño e implementación de un laboratorio de sistemas solares fotovoltaicos en la Universidad Antonio Nariño sede Riohacha - Fajardo Passo, Elmer Enrique; Puentes Garcerán, Robinson Evans (Universidad Antonio Nariño, 2022)
W, and by 2015 it reached an approximate total of 12 GW. This growth requires that educational institutions upgrade and innovate their teaching and training, guaranteeing an education of the highest quality.